17 university students receive RM500 aid from Larry Sng Education Fund - Borneo Post, (KK) (Borneo Post (KK), 2013)
ENGKILILI: A total of 17 university students received cash assistance from the Larry Sng Education Fund on Wednesday. These students who are from the rural areas of Engkilili, Batang Ai and Lubok Antu each received RM500 from the founder of the Fund, Larry Sng, who is also Sarawak Workers Party president.